THE ROLE OF SELF-ESTEEM IN COPING WITH CHRONIC ILLNESS: PSYCHOLOGICAL AND SOCIAL IMPLICATIONS - Faisal Malik (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Chronic illness affects millions of people worldwide and presents significant psychological and social challenges. Self-esteem plays a critical role in how individuals cope with the ongoing physical and emotional demands of chronic illness. This study examines the psychological and social implications of self-esteem in individuals managing chronic conditions such as diabetes, heart disease, and chronic pain. By exploring the relationship between self-esteem and coping mechanisms, the paper identifies key factors that influence recovery, emotional regulation, and overall quality of life. Findings suggest that higher levels of self-esteem correlate with more effective coping strategies, better emotional adjustment, and a greater sense of empowerment. This research underscores the importance of promoting self-esteem in treatment plans and support systems to enhance the well-being of individuals living with chronic illness.